Towards an embodied understanding of the sustainability of consumer choice—the case of fashion shopping - Solér, Cecilia (Frontiers in Sustainability, 2022)
This conceptual article uses an embodied theoretical lens to describe how consumption and shopping are bodily activities shaped by marketplaces. This article contributes to research on sustainable consumption in general and research on sustainable shopping in particular. The social and situated embodiment perspective highlights how sociomaterial marketplace elements configure shopping outcomes. The context of fashion shopping is used, and this article shows how an embodied view of shopping can increase our understanding of unsustainable shopping practices and promote shopping for sustainable products. This article aims to enrich the structural strand of sustainable consumption research by describing how the sustainability of individual shopping can be understood as skills and dispositions acquired within, or in relation to, marketplace activities and discourses. This suggests that current Western unsustainable fashion shopping practices, characterized by excessive consumption, change only if supply and communication practices in the fashion marketplace change.